Influence of carbohydrate mouth rinse on sprint performance: A systematic review and meta-analysis - de Oliveira, José Jonas; Crisp, Alex Harley [UNESP]; Barbosa, Carolina Gabriela Reis; e Silva, Alexandre de Souza; Baganha, Ronaldo Júlio; Verlengia, Rozangela (My University, 2017)
The purpose of this study was to investigate the influence of CHO mouth rinse on sprint performance during cycle ergometer and running tests. A systematic review and meta-analysis of randomized controlled studies were developed. The survey was conducted using the following databases: PubMed, SciELO, Cochrane, and Science Direct using the keywords: carbohydrate mouth rinse AND sprint. The search identified 41 articles of which 6 articles met the inclusion/exclusion criteria. The results of the meta-analysis indicate that CHO mouth rinse had no significant effect (P > 0.05) on the peak power (weighted mean difference [WMD] = 0.089 W·kg-1; 95% confidence interval [CI] = -0.823, 0.645) and mean power (WMD = 0.006; 95% CI = -0.365, 0.352) in the cycle ergometer test. In addition, no significant difference (P > 0.50) in the sprint running time (WMD = 0.009 sec; 95% CI = -0.068, 0.050) was observed. In conclusion, CHO mouth rinse does not influence short sprint performance.
Keywords: Carbohydrate; Mouth rinse; Sprint